272 Inherited peripheral neuropathies: analysis of PDXK gene identifies a new treatable disorder. Issue 12 (14th November 2019) - Chelban, Viorica; Wilson, Matthew; Zanetti, Natalia; Zamba-Papanicolaou, Eleni; Conte, Maria; Cordivari, Carla; Mills, Philippa; Wood, Nicholas; Clayton, Peter; Houlden, Henry
Abstract : Polyneuropathies are amongst the most common neurological conditions worldwide affecting over 20 million people. However, 40% of patients with primary polyneuropathies have no disease-causing mutation identified. We investigated patients with gene-negative primary polyneuropathies using a combination of whole genome sequencing, homozigosity mapping and segregation analysis. Pathogenicity was confirmed via enzymatic assays and mass spectroscopy on recombinant protein and patient-derived fibroblasts, plasma and erythrocytes. We used circular dichroism to show secondary structure changes and isothermal titration calorimetry to investigate the ATP binding. We report that biallelic mutations in human PDXK are associated with primary axonal polyneuropathy and optic atrophy. Pyridoxal kinase (PDXK) is involved in converting vitamin B6 to its active form, pyridoxal 5'-phosphate (PLP). We show that PDXK mutations lead to disease via decreased plasma PLP concentrations. Our functional studies revealed conformational rearrangement in the mutant enzyme around the kinase ATP-binding pocket with impaired PDXK ability to bind ATP and leading to reduced erythrocyte PDXK activity. We show that both the human clinical picture and biochemical profile in PDXK mutations are rescued by PLP supplementation. Patients regained their ability to walk independently. Furthermore, treatment-led normalisation of plasma PLP levels, correlated with reduction of neurofilament light chain concentrations, a biomarker of axonal breakdown. In conclusion, biallelic mutations in human PDXK are associated with a novel disorder leading to treatable primary axonal polyneuropathy and optic atrophy and identifies PLP as therapeutic target.